1991
DOI: 10.1007/bf00225236
|View full text |Cite
|
Sign up to set email alerts
|

Bending strength adjustments for moisture content for structural lumber

Abstract: This paper presents computer programs for adjusting the mechanical properties of 2-in. dimension lumber for changes in moisture content. Mechanical properties adjusted are modulus of rupture, ultimate tensile stress parallel to the grain, ultimate compressive stress parallel to the gain, and flexural modulus of elasticity. The models are valid for moisture contents from 8 to. 23 percent (assumed green value). Although test results can be adjusted for moisture content, such adjustments decrease in accuracy with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…Several publications provide mechanical properties of pine, agathis, meranti, and mahogany wood at air-dry conditions similar to this study's results (Table 5). Similar to many reports [18,[72][73][74], this study also finds that the mechanical properties of wet wood are consistently weaker than those of dry ones (Table 6). A similar phenomenon is valid for modulus of rupture (σ b ), shear strength parallel-to-grain (τ), tensile strength parallelto-grain (σ t ), maximum crushing strength (σ c ), compression stress perpendicular-to-grain at the proportional limit (σ c⊥pl ), compression stress perpendicular-to-grain at the 0.04" deformation (σ c⊥0.04 ), and modulus of elasticity (E) (Figure 4).…”
Section: The Mechanical Properties Difference Between Wet and Dry Woodsupporting
confidence: 90%
“…Several publications provide mechanical properties of pine, agathis, meranti, and mahogany wood at air-dry conditions similar to this study's results (Table 5). Similar to many reports [18,[72][73][74], this study also finds that the mechanical properties of wet wood are consistently weaker than those of dry ones (Table 6). A similar phenomenon is valid for modulus of rupture (σ b ), shear strength parallel-to-grain (τ), tensile strength parallelto-grain (σ t ), maximum crushing strength (σ c ), compression stress perpendicular-to-grain at the proportional limit (σ c⊥pl ), compression stress perpendicular-to-grain at the 0.04" deformation (σ c⊥0.04 ), and modulus of elasticity (E) (Figure 4).…”
Section: The Mechanical Properties Difference Between Wet and Dry Woodsupporting
confidence: 90%
“…It is well known that the moisture content of structural wood materials will directly affect its test strength value, and will also affect the subsequent determination of compressive design value [21]. Therefore, to unify the test strength value and compressive design value, each country often specifies a moisture content point as the reference point.…”
Section: Static Testing Methodsmentioning
confidence: 99%
“…High strains often indicate where damage will occur. 24 When the stress distribution in the xx direction was evaluated, the LVL samples showed similar stress distribution characteristics at half the load (F max /2). At the same time, it was observed that the stress in the support regions and the loading head area increased.…”
Section: Digital Image Correlation Resultsmentioning
confidence: 95%
“…The total reduction in edgewise loading was determined as 39%. Barrett and Lau, 24 in their study determining the moisture modeling of Douglas fir (Pseudotsuga menziesi) and southern pine (Pinus taeda L.) structural lumber, reported that increased moisture reduced bending strength (modulus of rupture -MOR). In Figure 7, the LVL modulus of elasticity values are given for 0-25% MC.…”
Section: Mechanical Test Resultsmentioning
confidence: 99%